General Insurer’s Financial Resilience Towards Catastrophe Risk: A Conceptual Framework (Issues in Social and Environmental Accounting (ISEA), 2025)
The changing climate has led to a significant increase in natural catastrophes worldwide,                posing unique challenges to the insurance industry. These catastrophic events, characterized by their infrequency and severe impact, demand specialized risk management approaches and place substantial pressure on insurer capitalization. The insurance industry is particularly vulnerable to the effects of climate change, with catastrophes representing significant financial hazards, including immediate reductions in earnings and statutory surplus, potential forced   asset liquidation, the risk of a rating downgrade, and the risk of insolvency. The failure of an insurance company can have far-reaching consequences for the economy, society, and the   nation as a whole. In this era of abrupt climate change and heightened catastrophe risk, the    resilience of insurers has become a critical concern. Understanding the extent to which these insurance companies can withstand increasing catastrophe risks is essential. However, measuring insurers’ resilience is complex and involves multiple factors across different dimensions including financial resilience, for which no clear measurement formula currently  exists. This study seeks to contribute to the literature by establishing the conceptual                      groundwork for understanding and measuring the financial resilience potential of general insurance companies, which may be valuable for researchers interested in empirical  investigations of this topic. Additionally, it extends the literature on the role of accounting in climate change risk management by demonstrating how insurance-specific accounting information can be used to assess insurers’ financial resilience. Finally, this study is expected to inform public policy discussions on climate change, particularly within the financial sector.